2021
DOI: 10.1002/jcla.24022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers associated with immune infiltration in papillary renal cell carcinoma

Abstract: Background Immunotherapeutic approaches have recently emerged as effective treatment regimens against various types of cancer. However, the immune‐mediated mechanisms surrounding papillary renal cell carcinoma (pRCC) remain unclear. This study aimed to investigate the tumor microenvironment (TME) and identify the potential immune‐related biomarkers for pRCC. Methods The CIBERSORT algorithm was used to calculate the abundance ratio of immune cells in each pRCC samples. Univariate Cox analysis was used to select… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The results further indicated that KNL1 played an important role in the development of PRAD. Interestingly, these KNL1-related molecules (e.g., BUB1, ASPM, TOP2A) have been implicated in immune infiltration in papillary renal cell carcinoma in another report (Deng et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The results further indicated that KNL1 played an important role in the development of PRAD. Interestingly, these KNL1-related molecules (e.g., BUB1, ASPM, TOP2A) have been implicated in immune infiltration in papillary renal cell carcinoma in another report (Deng et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, our study revealed TOP2A as the key hub gene in the PBMCs of individuals who received the second dose of COVID-19 mRNA vaccine, indicating a potential similarity between COVID-19 infection (live virus) and vaccination (spike protein of the virus) to some extent. Previous research on TOP2A primarily focused on kidney cancer, where its upregulation was associated with prognosis and considered a potential target for mRNA vaccine development [38][39][40][41][42][43][44][45][46]. TOP2A was upregulated in kidney cancer, could predict the prognosis, and might be a tumor target to guide mRNA vaccine development [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed as a candidate for peptide vaccine therapy in cancers like colorectal carcinoma and breast carcinoma [52,54,55]. In the context of nephropathy, studies on CEP55 have primarily focused on kidney cancer [41,44,[56][57][58][59][60]. Additionally, frameshift variants or deletions of CEP55 have been associated with polycystic kidneys [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…However, the immune role of BUB1B in BLCA remains undefined. Furthermore, BUB1B has been associated with immune infiltration in various tumors, such as prostate cancer, papillary renal cell carcinoma, and hepatocellular carcinoma (HCC) ( 30 - 32 ). In our immune infiltration analyses, BUB1B reduced CD8 + T cell, CD4 + T cell, macrophage, neutrophil, and dendritic cell enrichment, which validated the association of BUB1B with immune infiltration in BLCA.…”
Section: Discussionmentioning
confidence: 99%